Aleksander Bošković, Günther Schlee, a cura di, African political systems revisited: Changing perspectives on statehood and power, New York-Oxford, Berghahn Books, 2022, pp. 256 - Luciano Li Causi (Anuac, 2022)
Recensione di Aleksander Bošković, Günther Schlee, a cura di, African political systems revisited: Changing perspectives on statehood and power, New York-Oxford, Berghahn Books, 2022, pp. 256.